Effect of dentifrice containing crab-shell chitosan on the accumulation of dental plaque in fixed orthodontic appliances patients: A randomized controlled trial - J C. P Heryumani Sulandjari; Afina Zahra Chairunnisa; Ananto Ali Alhasyimi (Wolters Kluwer Medknow Publications, 2019)
Background: Patients with fixed orthodontic encounter problems in cleaning their teeth and mouths. Dental plaque tends to accumulate on wires, brackets, and surfaces between bonding materials and brackets. Plaque accumulation increases the risks of decalcification, caries, and gingivitis. Chitosan extract is a potential antibacterial agent and inhibitor of dental plaque formation. This study aims to assess the effectiveness of chitosan-containing dentifrice in decreasing plaque accumulation in patients with fixed orthodontic appliances. Materials and Methods: This was a prospective, randomized, double-blind study which involved 32 samples (randomly allocated to the control and chitosan groups, after the power of the study was considered) from patients with orthodontic appliances undergoing the last stage of fixed active orthodontic treatment. Plaque accumulation before and after dentifrice use was measured using a plaque index according to O'leary, before and after using toothpaste within 5 days. The patients were instructed to brushing with chitosan-containing dentifrice and chitosan-free dentifrice as a control. Washout period that needed between brushing with chitosan-containing dentifrice and chitosan-free dentifrice as a control was 7 days. Each mouthwash used routinely for 5 days with the same duration and intensity. The data obtained was then analyzed with one-way analysis of variance followed by post hoc least significant difference. The level of significance was set as 0.05. Results: Plaque accumulation before and after dentifrice use significantly differed (P < 05) between the control and chitosan groups. The average reductions in plaque accumulation were greater in the chitosan group and control group brushing using chitosan-containing dentifrice. Conclusion: Dentifrice-containing chitosan more effectively reduces dental plaque accumulation in patients with fixed orthodontic appliances than dentifrice without chitosan.